2020
DOI: 10.15176/vol57no207
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Heritage-Based Urban Festival as a Tool to Promote Local Identity and City Marketing

Abstract: This paper deals with the processes of transformation of an urban festival – the Radvaň Fair in the city of Banská Bystrica, Slovakia – in a comprehensive way and from a chronological point of view. The main focus is on the development of the festival in the post-1989 (post-communist) period. The fair has been organised continuously since 1655 and went through a number of transformations. Its function has changed from a primarily commercial event of three centuries to a significant cultural and social hallmark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…According to Kim et al [ 10 ], consumption by tourists of previously unknown local dishes is one of more exciting experiences in tourist destinations. Moreover, Bitušíková [ 70 ] found that regional dishes are often sold during fairs and festivals which strengthen the identity of the locals, evoke feelings of solidarity and pride, are a means of restoring cohesion and bonds within the local community and promote the region. Similar conclusions were drawn by Teodoroiu and Tudorache [ 71 ], who claim that fairs and festivals are the most important events promoting the region’s intangible culture and culinary heritage.…”
Section: Discussionmentioning
confidence: 99%
“…According to Kim et al [ 10 ], consumption by tourists of previously unknown local dishes is one of more exciting experiences in tourist destinations. Moreover, Bitušíková [ 70 ] found that regional dishes are often sold during fairs and festivals which strengthen the identity of the locals, evoke feelings of solidarity and pride, are a means of restoring cohesion and bonds within the local community and promote the region. Similar conclusions were drawn by Teodoroiu and Tudorache [ 71 ], who claim that fairs and festivals are the most important events promoting the region’s intangible culture and culinary heritage.…”
Section: Discussionmentioning
confidence: 99%
“…For university freshmen a campus tour can improve their sense of place through guided tours and self-guided walks with the help of brochures (Barlett, 2002). On a larger scale, cultural urban festivals can also be a tool to enhance (Kádár and Klaniczay, 2022) and to promote (Bitušíková, 2020) the sense of place to visitors and citizens alike.…”
Section: Sense Of Placementioning
confidence: 99%
“…The analysis of the commercial-learning event Valentine's Weekend at the Castle showed that the subject of commodification of cultural heritage in Slovakia is not only (or predominantly) elements of folk culture (e.g., Popelková, Zajonc, 2013;Koštialová 2016Koštialová , 2020Bitušíková, 2020Bitušíková, , 2021, but also elements of high culture, such as historical objects as a space for the event, historical clothing in the form of replicas, or realities about the way of life and events from the life of higher social classes in the form of narratives that thematically correspond to the content of Valentine's Day used during the event.…”
Section: Summar Ymentioning
confidence: 99%